Information Seeking Behaviors of Academicians in the Field of Social Sciences - Mithat Baver ZENCİR (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
When library and information science is considered, it is hard to say that there have been sufcient studies on social scientists' information behaviors in Turkey. It is inevitable that this situation will have a negative effect on information services offered for social scientists. This study aims to provide information which will enable information centers to get to know the abovementioned group closer, and to offer them suggestions about services or resources that will be provided to this group by evaluating information behaviors of social science academics of İzmir Kâtip Çelebi University. For this purpose, 63 out of 103 (61%) academics in the eld of social sciences were contacted. In this research descriptive method was conducted, and, questionnaires were used as a data collection method. The ndings show that academics need information rstly for scientic studies, and they give more importance to journals and books among other information resources. Some eld-specic resources are also used by academics who participated in the research. While the use of library is considered important in this eld, the use of personal resources, tracking citations and using search engines are the main methods for searching information and literature. Electronic resources tend to be more widely used compared to printed ones in this eld, and the academics use libraries remotely on the internet. Especially e-journals and older issues of e-journals are sought for. The biggest problems with regard to the use of electronic resources and libraries are the difculty of reaching older issues and inadequacy of collections respectively. The ndings reveal a signicant point, that is, users in this eld do not ask for help from a librarian and they are not at the expected level regarding the possession of information literacy skills. In this study, social scientists' approach to the open access is also researched, and it is seen that this group's perception of open access is conicting and problematic. These ndings within the scope of this research are interpreted in comparison with the similar research in the literature.